The Family-Centered Care Approach in Optimizing Child Care in Health Facilities - Purnamasari, Juni (Oshada, 2025)
This study aims to analyze the influence of the Family-Centered Care (FCC) approach on the optimization of child care in health facilities. FCC is a service approach that positions the family as an active partner in the child care process through open communication, participation in medical decision-making, and respect for family values and culture. The research method used is quantitative analytic with a cross-sectional design. The sample consisted of 100 parents or caregivers of children receiving care at health facilities, selected using purposive sampling techniques. The data collection instrument was a closed-ended questionnaire using a Likert scale that had been tested for validity and reliability. The analysis results showed a strong and significant relationship between the implementation of FCC and the quality of child care (r = 0.624; p < 0.05), as well as a significant positive influence in the regression test (R² = 0.384). The conclusion of this study indicates that the FCC approach greatly contributes to improving child comfort, family satisfaction, and the effectiveness of the healing process. Strengthening policies and healthcare worker training is necessary to encourage comprehensive implementation of FCC.